School and human formation: an ever-postponed proposal - Valle, Lílian de Aragão Bastos do; Bantim Frambach, Danilo (Revista de Educação PUC-Campinas, 2021)
The public school was born as an institution responsible for the common formation of citizens, for their insertion in the same culture, thus forming a nation. However, the victory of liberalism very early transformed this task into an instructional practice, relegating the body, the arts, and the human sensitivity to an accessory place in the school path. On the other hand, nowadays, the institution’s monopoly over public education is threatened by the revolution in information and communication technologies, responsible for an overwhelming cultural transformation. With all these challenges, how could one think about school today? Would it be possible, given the individualism and immediacy of contemporary society, to think of its task as the practice of human formation? To answer these questions, this paper aims to analyze the historical moment that made possible the birth of cognitivism, its impacts on the idea of public school and how, along with the liberal project, it ignored the body in the process of human formation, reducing it to the simple task of instruction. Moreover, this work aims to make a critical exam of the employment of digital media in education, since it represents not only new possibilities for the school to revive the human formation ideal, but also new challenges to the public school project.